Aortic Coarctation a Systemic Vessel Disease—Insights from Magnetic Resonance Imaging - Eichhorn, Joachim G.; Ley, Sebastian; Kropp, Florian; Fink, Christian; Brockmeier, Konrad; Loukanov, Tsvetomir; Ley-Zaporozhan, Julia (The Thoracic and Cardiovascular Surgeon, 2019)
Background Even after successful aortic coarctation (CoA) repair, hypertension causes premature morbidity and mortality. The mechanisms are not clear. The aim was to evaluate elastic wall properties and aortic morphology and to correlate these results with severity of restenosis, hypertension, aortic arch geometry, noninvasive pressure gradients, and time and kind of surgical procedure.Methods Eighty-nine patients (17 ± 6.3 years) and 20 controls (18 ± 4.9 years) were examined using magnetic resonance imaging (MRI). In addition to contrast-enhanced MR angiography and flow measurements, CINE MRI was performed to assess the relative change of aortic cross-sectional areas at diaphragm level to calculate aortic compliance (C).Results Fifty-four percent of all patients showed hypertension (> 95th percentile), but more than half of them had no significant stenosis (defined as ≥30%). C was lower in CoA than in controls (3.30 ± 2.43 vs. 4.67 ± 2.21 [10–5 Pa–1 m–2]; p = 0.024). Significant differences in compliance were found between hyper- and normotensive patients (2.61 ± 1.60 vs. 4.11 ± 2.95; p = 0.01), and gothic and Romanesque arch geometry (2.64 ± 1.58 vs. 3.78 ± 2.81; p = 0.027). There was a good correlation between C and hypertension (r = 0.671; p < 0.01), but no correlation between C (and hypertension) and time or kind of repair, restenosis, or pressure gradients.Conclusion The decreased compliance, a high rate of hypertension without restenosis, and independency of time and kind of repair confirm the hypothesis that CoA may not be limited to isthmus region but rather be a widespread (systemic) vascular anomaly at least in some of the CoA patients. Therefore, aortic compliance should be assessed in these patients to individually tailor treatment of CoA patients with restenosis and/or hypertension.
Keywords: aortic coarctation; surgical repair; hypertension; arch geometry; compliance; systemic vessel disease